1 - 4x^2 Factorization using the formula: a^2 - b^2 = (a + b) (a - b)
2 answers:
Answer:
Yes
Step-by-step explanation:
Factorise using the difference of squares, that is
a² - b² = (a + b)(a - b)
Given
1 - 4x², then a = 1 and b = 2x
= (1 + 2x)(1 - 2x) = (1 - 2x)(1 + 2x)
Since multiplication is commutative order is not important, that is
3 × 4 = 4 × 3
Answer:
1 - 4x^2
=(1)^2 - (2x)^2
=(1-2x) (1+2x)
it could also be written as (1 + 2x) (1 - 2x)
Step-by-step explanation:
the order doesn't matter because it's a multiplication
You might be interested in
If tan x = .56, then cot x is 1.79
Answer:
C
Step-by-step explanation:
The key word is x-axis, and since the bottom line is the x, just look for a reflection of it.
Answer:
-5
Step-by-step explanation:
7 times 7 times 7 times 7 times 7 times 7 times 7 times 7 times 7 times 7
Answer:
sure
Step-by-step explanation: